Venous Ulcer - Santoso, Irene Dorthy; Nilasari, Hanny; Yusharyahya, Shannaz Nadia (UI Scholars Hub, 2017)
Leg ulcers one common problem in the adult population to geriatric with a prevalence about 1-2%. The pattern of life which tends to be sedentary, less activity, obesity, increased the incidence of leg ulcers. The duration of healing and recurrence occurs in majority of patients contributed the decline in quality of life for patients with venous ulcers. Diagnosis, latest treatment and prevention are essential to discuss.